KOMPLEKS MAKAM KUNA DI DESA LORAM KULON POSISI DAN KRONOLOGI SITUS DALAM KERANGKA SEJARAH KOTA KUDUS - Muhammad Chawari (BRIN, 2010)
The new discovery of an old graveyard in Kiringan hamlet, Loram Kulon village, Jati subdistrict, Kudus regency, Central Java province adds another Islamic site to the long list of Islamic sites found around the old city of Kudus. This paper discusses the temporal and functional dimensions of this graveyard in the history of Kudus area. Considering some available evidence, it is proposed here that chronologically, the site can be dated back to a period around early 16